Factitious disorder with self inflicted injuries (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
A 45 year old Bangladeshi female presented with multiple deep cuts and scratch injuries on her body. It was evident from the detail history and observation that the injuries were done by the patient herself. The absences of any obvious external rewards lead to the diagnosis of the factitious disorder. Deception is a key component in both malingering and factitious disorder but in factitious disorder, getting attention or playing the sick role is the only motive.